Factors Affecting the Quality of Microscopic Tuberculosis Examination in Madiun, East Java: A Multilevel Analysis - Sri Hartini; Endang Sutisna Sulaeman; Bhisma Murti (Journal of Health Policy and Management, 2018)
Background: Tuberculosis (TB) remains major cause of morbidity and mortality due to any one of infectious agent worldwide. In low income countries, Ziehl-Neelsen sputum smear microscopy is the only cost-effective tool for diagnosis and monitoring of patients on treatment. Refresher training for laboratory professionals involved in Acid Fast Bacilli (AFB) microscopy at peripheral health facilities is important. This study aimed to assess factors affecting the quality of microscopic tuberculosis examination in Madiun, East Java, using a multilevel analysis model.Subjects and Method: A cross-sectional study conducted at 23 puskesmas (community health centers) in Madiun, East Java, from March to April 2018. A sample of 230 preparations was selected by simple random sampling. The dependent variable was quality of microscopic TB examination. The independent variables were tenure, refresher training, and accreditation status of puskesmas. The data were collected by questionnaire and analyzed by a multilevel logistic regression.Results: Quality of microscopic TB examination was positively associated with tenure ?3 years (b= 2.77; 95% CI= 0.81 to 4.73; p= 0.006) and accredited community health center (b= 3.06; 95% CI= 0.81 to 4.62; p<0.001). The association between refresher training and quality of microscopic TB examination was not statistically significant (b= -0.51; 95% CI= -2.33 to 1.32; p= 0.580). Puskesmas had a contextual effect on quality of microscopic TB examination with ICC= 22.01%.Conclusion: Quality of microscopic TB examination is positively associated with tenure and accredited puskesmas. Refresher training for laboratory technicians was not effective in improving the quality of microscopic TB examination Puskesmas has a considerable contextual effect on quality of microscopic TB examination.Keywords: microscopic TB examination, quality, tenure, community health center, accreditation, multilevel analysisCorrespondence: